Neonates With Complex Cardiac Malformation and Congenital Diaphragmatic Hernia Born to SARS-CoV-2 Positive Women—A Single Center Experience. Issue 6 (November 2020) - Goldshtrom, Nimrod; Vargas, Diana; Vasquez, Angelica; Kim, Faith; Desai, Kinjal; Turner, Mariel E.; Barry, Oliver; Torres, Alejandro; Levasseur, Stéphanie; Strletsova, Svetlana; Gupta, Palka R.; Defazio, Jennifer R.; et al.
Background: Our understanding of the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on pregnancies and perinatal outcomes is limited. The clinical course of neonates born to women who acquired coronavirus disease 2019 (COVID-19) during their pregnancy has been previously described. However, the course of neonates born with complex congenital malformations during the COVID-19 pandemic is not known. Methods: We report a case series of seven neonates with congenital heart and lung malformations born to women who tested positive for SARS-CoV-2 during their pregnancy at a single academic medical center in New York City. Results: Six infants had congenital heart disease and one was diagnosed with congenital diaphragmatic hernia. In all seven infants, the clinical course was as expected for the congenital lesion. None of the seven exhibited symptoms generally associated with COVID-19. None of the infants in our case series tested positive by nasopharyngeal test for SARS-CoV-2 at 24 hours of life and at multiple points during their hospital course. Conclusions: In this case series, maternal infection with SARS-CoV-2 during pregnancy did not result in adverse outcomes in neonates with complex heart or lung malformations. Neither vertical nor horizontal transmission of SARS-CoV-2 was noted.